The Piltdown forgery (Oxford University Press, 2003)
Cover; Contents; Introduction to the fiftieth anniversary edition of The Piltdown Forgery; Some characters in the Piltdown story; Preface; Note to second impression; Illustrations; 1. A Darwinian prediction; 2. An impasse; 3. An hypothesis; 4. The jaw displaced; 5. Flint and fauna; 6. The full extent; 7. The principals and their part; 8. Some others; 9. Lineaments of the forger; 10. Events reconsidered; 11. Entanglement; 12. 'The eye wink'; 13. The Sussex wizard; 14. The question of complicity; Epilogue; Afterword: Piltdown 2003; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; R; S; T.